E-learning courseware for driving lesson / Mohd. Fuad Kamaludin - Kamaludin, Mohd. Fuad (2012)
Driving lesson is the most important thing to learn before becoming a legal driver. For someone to succeed to be a driver, they need to follow the procedures that were arranged and agreed by Jabatan Pengangkutan Jalan (JPJ). Driving school institution is an organization that was assigned by JPJ to teach the driving lesson in order for citizens of Malaysia to get driving license. The method used in almost every driving school institution in Malaysia was the traditional classroom that is lectures and reading books. These institutions also provide a practical lesson on simulating the cars after students of driving school pass their on the theory course. From the student's perspective, the institution does not have an efficient driving lesson lecture due to the time constraint, lack of attention and also unattractive method used. After all information had been gathered, an e-learning courseware that based on electronic study is the way to solve this problem. E-learning courseware for driving lesson is providing learning through electronic devices that cover almost all the theory course. The significance of this project can be divided into two that is to the students and also the instructors. For the instructors, this project was helping the instructors to give better understanding regarding driving lesson. As for students, this project will help them to understand more on the topic of Highway Code and rules on the road. It had also helped them to know the right way to drive in real situation. There are three (3) objectives to achieve, to identify and analyze the requirements of elearning for driving lesson courseware prototype, to design a courseware for driving lesson and to develop and demonstrate an interactive e-learning courseware for driving lesson. For this development, System Development Life Cycle (SDLC) was adapted to be the methodology to guide in the development processes. The phases involve are problem identification and planning, requirement gathering and analysis, design and develop. After finish the requirement gathering and analyze requirement, the deliverables are use to design the storyboard of e-learning courseware for driving lesson. Using storyboard as guidance, it was used to develop the courseware.